Тарзан: [перевод с английского] / Э. Р. Берроуз ; пер. Э. К. Бродерсен - Берроуз Эдгар Райс (1991)
Экземпляры: (20210426) / Инвентарный номер: 23854 / Цена: / Сис.шифр: 84(4/8) / Авт.знак: Б 51 / ББК: 84(7Сое)